Concilier biodiversité et agriculture : dépasser la dualité du land sparing contre le land sharing - Marie Saydeh; Jean-François Bissonnette (VertigO, 2024)
Biodiversity loss is a threat to human survival and more explicitly to populations that are closely dependent of various natural resources. Particular agricultural practices have irreversibly simplified ecosystems, affecting global biodiversity. Likewise, the compelling necessity to conciliate biodiversity and agriculture has led to the production of valuable scientific knowledge, such as the land sparing versus land sharing debate. The land sparing approach promotes the intensification of agriculture and the creation of biodiversity conservation areas, while the land sharing approach tends to value functional biodiversity into agricultural systems. The impact of this debate in the elaboration of policies needs to be considered with caution. For example, land sparing can lead to measures that either enable actors that practice substantial intensive agriculture or disadvantage smaller farmers with limited resources. The duality on which the land sparing vs. land sharing debate is articulated tends to limit the attention given to more nuanced arguments. Out of ethical consideration for the less affluent and represented populations in this specific research display, we suggest to overcome the state of debate in order to avoid imposing one approach over the other. For future research prospects, it seems to be preferable to study socio-economical contexts in which agriculture is practiced, as well as the specific relationships between farmers and biodiversity.